Eight new species of Scissurellidae and Anatomidae (Mollusca: Gastropoda: Vetigastropoda) from around the world, with discussion of two new senior synonyms - Geiger, Daniel L. (Zootaxa, 2006)
Eight new species of Scissurellidae and Anatomidae are described: Scissurella kaiserae new species from the Panamic; Scissurella lorenzi new species from the Indo-Malayan archipelago; Scissurella maraisorum new species from South Africa; Sinezona garciai new species from the Caribbean; Sinezona globosa new species from the tropical Western Pacific; Sinezona macleani new species from the Philippines; Sinezona singeri new species from the Red Sea; and Anatoma jansenae new species from southern Australia. Radulae of Scissurella kaiserae and Sinezona singeri are illustrated. Anatoma munieri (Fischer, Oct. 1862) is identified as a senior synonym of Anatoma turbinata (A. Adams, Nov. 1862), and Sukashitrochus morleti (Crosse, 1880) is shown to be a senior synonym of Sukashitrochus indonesicus Bandel, 1998, and Sukashitrochus simplex Bandel, 1998. These synonymies are based on examination of type material in the Muséum Nationale dHistoire Naturelle, Paris; scanning electron microscope images of the types are provided, and lectotypes are here selected.